ANTROPOLOGIENS HEMMELIGHED: Refleksioner over etnografens rolle i studiet af hemmelige ritualer - Højbjerg, Christian Kordt (Tidsskriftet Antropologi, 1995)
Christian Kordt Højbjerg: The Secret of Anthropology. Reflections on the Ethnographer’s Role in the Study of Secret Rituals. The article gives an account of an apparently hopeless effort to study men’s secret association and its masked figure among the Loma in Guinea. The secret mask is purposely withheld during the ethnographer’s stay, and he is not allowed to assist in the meetings of the men’s society taking place in the sacred grove. However, the student possesses prior knowledge about the mask, and information from the meetings is transmitted constantly. Therefore, nothing is in faet held secret to the ethnographer, and the leaders of the men’s association seem to be aware of it. Still, secrecy is being practiced by the people chosen as the object of study. An essential aspect of secrecy is hereby revealed. Despite its emptiness, it is efficient in its patteming of social relations. The methodological point is that in anthropology, subjectivity can be a means to objectivity. Not by focusing too exelusively on the observing scientist, but rather in the sense that the staging of the ethnographic encounter by the anthropologist produces a miscalculation permitting an understanding of the scientific object. A sort of role inversion is taking place. The anthropologist realizes that he has become the victim of an illusion about the nature of secrecy, and that he has been subjected to the practice of secrecy. This lived experience leads to a concluding observation about the common but reversed strategies of staging inherent in secrecy and anthropology. While secrecy deliberately and inevitably reveals a part of itself in order to conceal, anthropology is on the contrary inevitably concealing reality when constructing its object. But just as secrecy implies concealment, anthropology is compelled to unmask reality, at least as a regulative principle, if it is not to lose its status as a scientific discipline.